Managerial Capitalism Ownership, Management and the Coming New Mode of Production - Lévy, Dominique (Pluto Press, 2018)
The debate around growing inequality is raging amongst economists, and Marxists are finding new ways to map-out the modern economy. Managerial Capitalism introduces a new way of understanding the changing structure of our economy through the emergence and behaviour of a new class - managers. In the post war years as social democracy reigned, managers tended to form compromises with workers. However, under neoliberalism, allegiances have shifted. Today, a new alliance is forming between managers and capitalist owners, changing the nature of the hierarchy of power under capitalism. Additionally, the authors argue, this is happening much faster and universally than was previously thought.By applying Marx's basic concepts to the reality of the system today, through the use of extensive data sets as well as firmly rooting the argument in its historical context, Managerial Capitalism updates Marxism for the twenty-first century, through showing how the modes of production today are shaped by a new class, that must be understood if it is to be challenged.